Contrast Enhanced Subsurface Fingerprint Detection Using High-Speed Optical Coherence Tomography - Yu, Xiaojun (2017)
Spectral-domain optical coherence tomography (SD-OCT) has been demonstrated to be a viable tool in forensic science for fingerprint detection, yet it still suffers from certain practical issues, e.g., the limited scanning speed and low image contrast. In this letter, we report a high-speed SD-OCT together with an image contrast enhancement mechanism for reliable subsurface fingerprint detection. The constructed SD-OCT system achieves a scanning rate up to 60k A-lines/s, and thus, both 3D volumetric images, reaching up to 20 mm × 20 mm × 1.2 mm, and en face internal fingerprint furrow pattern images could be obtained. Based upon the analyses of the papillary layer anatomical structures, the contrast enhancement technique not only suppresses image artifacts, but also is effective in detecting fingerprint spoofing. Experiments on healthy subjects have also been conducted to verify the system imaging capability and the effectiveness of the contrast-enhancement technique.